The homeostasis of iron, copper, and zinc in paracoccidioides brasiliensis, cryptococcus neoformans var. Grubii, and cryptococcus gattii: a comparative analysis - Silva, Merelle Garcia; Schrank, Augusto; Bailão, Elisa Flávia L. C.; Bailão, Alexandre Melo; Borges, Clayton Luiz; Staats, Charley Christian; Parente, Juliana Alves; Pereira, Maristela; Izaac, Silvia Maria Salem; Mendes-Giannini, Maria José Soares [UNESP]; Oliveira, Roseli Maria Zancopé; Silva, Livia K. Rosa e; et al. (Frontiers, 2011)
Iron, copper, and zinc are essential for all living organisms. Moreover, the homeostasis of these metals is vital to microorganisms during pathogenic interactions with a host. Most pathogens have developed specific mechanisms for the uptake of micronutrients from their hosts in order to counteract the low availability of essential ions in infected tissues. We report here an analysis of genes potentially involved in iron, copper, and zinc uptake and homeostasis in the fungal pathogens Paracoccidioides brasiliensis, Cryptococcus neoformans var. grubii, and Cryptococcus gattii. Although prior studies have identified certain aspects of metal regulation in Cryptococcus species, little is known regarding the regulation of these elements in P. brasiliensis. We also present amino acid sequences analyses of deduced proteins in order to examine possible conserved domains. The genomic data reveals, for the first time, genes associated to iron, copper, and zinc assimilation and homeostasis in P. brasiliensis. Furthermore, analyses of the three fungal species identified homologs to genes associated with high-affinity uptake systems, vacuolar and mitochondrial iron storage, copper uptake and reduction, and zinc assimilation. However, homologs to genes involved in siderophore production were only found in P. brasiliensis. Interestingly, in silico analysis of the genomes of P. brasiliensis Pb01, Pb03, and Pb18 revealed significant differences in the presence and/or number of genes involved in metal homeostasis, such as in genes related to iron reduction and oxidation. The broad analyses of the genomes of P. brasiliensis, C. neoformans var. grubii, and C. gattii for genes involved in metal homeostasis provide important groundwork for numerous interesting future areas of investigation that are required in order to validate and explore the function of the identified genes and gene pathways.